Komparasi Kinerja Keuangan Menggunakan Metode Camel pada Bank Konvensional dan Bank Digital Tahun 2021-2024 Selama Masa Pandemi dan Transisi Pandemi Covid-19 - Fidela Rizki Ananda; Ifan Wicaksana Siregar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to compare the financial performance of conventional and digital banks in Indonesia during the 2021–2024 period, covering the Covid-19 pandemic and the post-pandemic transition. The analysis method used is CAMEL (Capital, Asset Quality, Management, Earnings, and Liquidity) with indicators including Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Net Profit Margin (NPM), Return on Assets (ROA), Operating Expenses to Operating Income (BOPO), and Financing to Deposit Ratio (FDR). This research employs a quantitative approach with a descriptive comparative method involving six sample banks, consisting of three conventional banks and three digital banks listed on the Indonesia Stock Exchange. The data used are annual financial reports published during the research period. The findings indicate significant differences in several financial ratios, particularly CAR and NPL, between conventional and digital banks. In general, digital banks have higher capital ratios and lower NPLs, while conventional banks show more stable performance in profitability and operational efficiency ratios. These results can serve as a reference for banks and stakeholders in formulating post-pandemic business strategies.